Midnight Crossing - Roger Holzberg; Travanti, Daniel, J., 1940-; John Laughlin; Kim Cattrall; Faye Dunaway (USA Limelite Studios, 1988)
A group of adventurers sneak into Cuba to try to recover
A group of adventurers sneak into Cuba to try to recover
Roger Holzberg
Language: English Subtitles : No Subtitle
Keywords: Thriller; Mystery